Nurses' Work Motivation Influences Handwashing Compliance Before and After Five Moments at A General Hospital in Banjarmasin - Noor Amaliah; Amalia Salsabila; Dewi Kartika Wulandari; Muthmainnah Muthmainnah (Malahayati Nursing Journal, 2026)
ABSTRACT Healthcare-associated infections (HAIs) are a major concern, often linked to healthcare workers' hand hygiene. Adherence to "Five Moments" hand hygiene is crucial for prevention. This study examined the relationship between nurses' work motivation and hand hygiene compliance at hospital in Banjarmasin. A quantitative, cross-sectional, observational analytic design was employed. Ninety-three inpatient nurses were included via total sampling. Data on work motivation (questionnaire) and hand hygiene compliance (observation) were collected. Univariate and bivariate (Spearman Rank) analyses were performed. Results: ost nurses (78%) exhibited strong work motivation. Hand hygiene compliance varied: higher for moments 4 (70%) and 5 (87%), but lower for moments 1 (41%), 2 (32%), and 3 (51%). Overall, 68% were compliant, while 32% were less or non-compliant. A significant moderate positive correlation (p 0.001, r = 0.447) was found between work motivation and hand hygiene compliance. Discussion: Strong motivation correlates with better hand hygiene, reducing infection risk. The gap between knowledge and practice, particularly in critical moments, highlights the need for comprehensive interventions. Enhancing nurses' motivation through support, training, and recognition can improve compliance, thereby boosting patient safety and service quality. Keywords: Compliance, HAIs, Hand Hygiene, Nurses, Work Motivation.